Geometry Improvement and Flow Simulation in the water level control valve based on the CAD/CAE and DOE integrated system - Nguyen Huu Tho; Phan Hoang Phung; Huynh Van Nam; Nguyen Vu Anh Duy (Jurnal POLIMESIN, 2021)
Floating valve is a type of valve which can open and close automatically based on the level of water in the tank by Archimedes force without using electric-based control signals. However, there are no engineering reports of the influences of factors to the liquid flow through the valve with the considerations of multiple objective obtimization based on design of experiments (DOE) in the context of our country until now. Many products in the domestic market have been paid more attention by the customers but still have several disadvantages such as the practical malfunctions of floating valve. Thus, this study presents an integrated approach of CFD simulation and DOE-based multi-criteria optimization for proposed valve design. This technique allows to identify the influencing factors to the valve’s goals of volume flow rate and the force which exerts into the rubber rubber to create a gap distance in order that the float valve can operate. In this study, several factors used as inlet pressure, a gap distance of rubber sheet, pressure vent hole diameter and orifice diameter. CFD (computational fluid dynamics) based simulation technique integrated into experimental design assists us to determine the most suitable dimensional and operational parameters of water level-control float valve. The numerical simulation results confirmed that design valve are appropriate and potential in the practice. The integrated simulation framework can be considered a general and effective way to analyze several types of other valves.